Peningkatan Pemahaman Perkoperasian bagi Anggota dan Non Anggota KOPSIS Melalui Pengenalan Digitalisasi Layanan di Koperasi Siswa (KOPSIS) SMAN Jatinangor Kabupaten Sumedang Jawa Barat - Nugraha, Agus (E-Coops-Day, 2025)
Student Cooperative (KOPSIS) is a cooperative business unit located within the school environment, whose members are students of that school and can engage in economic activities without a legal business entity (notarial deed). KOPSIS's existence does not necessarily translate into all pupils being members right away. usually brought on by two factors: the unequal dissemination of information regarding cooperatives and the advantages of joining KOPSIS. In order to help students better understand cooperatives and KOPSIS's presence in their school, one way to promote and socialize about the organization is to provide training to administrators, members, and potential members on how digital technology can be adapted into KOPSIS services. Using this method, KOPSIS will become more attractive, contemporary, modern, and facilitate services to members, which is ultimately expected to increase students' interest in becoming members of the KOPSIS.